Collision with power lines and electrocutions in birds — an analysis based on Swedish ringing recoveries 1990–2017 - Fransson, Thord; Jansson, Lina; Kolehmainen, Tuomo; Wenninger, Thomas (Ornis Svecica, 2019)
Recoveries of birds ringed in Sweden from the period 1990–2017 were used to analyse the occurrence of collisions with power lines and electrocutions. Out of more than 10,000 recoveries of birds found dead with finding circumstances mentioned, 8.6% was associated with power line constructions. The number of species involved was 51 and high proportions were especially evident in some species of owls and raptors. The overall proportion of recoveries caused by collision / electrocution shows a significant decrease over time. A decrease over time in the proportions of electrocution and collision was also evident when analysing finding circumstances in four species where corpses were sent to the Swedish Museum of Natural History. Information about the power line system in Sweden during the period 2007–2016 shows that the length of local power lines has decreased with about 21% during a ten-year period and that underground cables have increased with 28% during the same period. The results show that collisions with power lines have decreased more than electrocutions and this may imply that there are still many places where birds are at risk of being electrocuted.